The Policy of Islamic Economic Politics in Indonesia in the Reformation Era - Choirunnisak Choirunnisak; Nopriawan Mahriadi (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2022)
The Reformation Era began on May 21, 1998, with Suharto's resignation as president of Indonesia being replaced by B.J. Habibie. This study discusses how the political economy of Islam in Indonesia is, especially in the Reformation era. This research is a type of library research (library research) that focuses on qualitative data management with data analysis methods using descriptive-analytical methods. The results of this study are six Islamic political-economic policies 1) Law Number 10 of 1998 concerning banking. 2) Law Number 23 of 1999 concerning Bank Indonesia. 3) Law number 3 of 2004 concerning Bank Indonesia. 4) Law number 24 of 2004 concerning the Deposit Insurance Corporation. 5) Law number 19 of 2008 concerning Indonesian Sharia Securities. 6). Law No. 21 of 2008 concerning Islamic banking